Macitentan in Pulmonary Arterial Hypertension Due to Congenital Heart Disease (CHD-PAH): Real-World Evidence from the OPUS/OrPHeUS Studies - Kelly M. Chin; Richard Channick; Nick H. Kim; Rose Ong; Stefano Turricchia; Nicolas Martin; Lada Mitchell; Vallerie V. McLaughlin (Cardiology and Therapy)
Abstract Introduction Data on real-world clinical practice and outcomes of patients with pulmonary arterial hypertension (PAH) associated with congenital heart disease (CHD) are scarce. The OPUS/OrPHeUS studies enrolled patients with PAH newly initiating macitentan, including those with PAH associated with CHD (CHD-PAH). Methods OPUS was a prospective, United States, multicenter, long-term, observational drug registry (April 2014–June 2020). OrPHeUS was a retrospective, United States, multicenter medical chart review (October 2013–March 2017). The characteristics, treatment patterns, safety, and outcomes during macitentan treatment of patients with CHD-PAH and the subgroups Eisenmenger syndrome, left-to-right shunts and small/coincidental CHD were descriptively compared. Results The combined OPUS/OrPHeUS population included 272 (6.1%) patients with CHD-PAH (80 patients with Eisenmenger syndrome; 82 patients with left-to-right shunts and 92 patients with small/coincidental defects). Most patients across the CHD-PAH subgroups were in World Health Organization Functional Class II/III (82.9–94.6%). Macitentan was initiated as combination therapy in 65.0% of patients with CHD-PAH. During follow-up, 81.4% of patients experienced ≥ 1 adverse event (AE), the most common being dyspnea (23.5%), nausea (13.7%), dizziness (12.7%), headache (12.7%) and edema (10.8%). The 1- and 2-year Kaplan–Meier (95% confidence limits) estimates of patients with CHD-PAH being free from hospitalization were 64.5% (57.9, 70.4) and 49.3% (41.9, 56.3); for survival, the 1- and 2-year Kaplan–Meier estimates were 93.5% (89.3, 96.1) and 90.2% (84.9, 93.7). Conclusions Macitentan was used in clinical practice in patients with CHD-PAH and its subgroups, including as combination therapy in the majority of patients. Safety in this population was consistent with the known profile of macitentan. Trial Registration OPsumit® Users Registry (OPUS): NCT02126943; Opsumit® Historical Users cohort (OrPHeUS): NCT03197688; URL www.clinicaltrials.gov .